Substituted Hydroxyapatites with Antibacterial Properties - Kolmas, Joanna (Hindawi Publishing Corporation, 2014)
Reconstructive surgery is presently struggling with the problem of infections located within implantation biomaterials. Of course, the best antibacterial protection is antibiotic therapy. However, oral antibiotic therapy is sometimes ineffective, while administering an antibiotic at the location of infection is often associated with an unfavourable ratio of dosage efficiency and toxic effect. Thus, the present study aims to find a new factor which may improve antibacterial activity while also presenting low toxicity to the human cells. Such factors are usually implemented along with the implant itself and may be an integral part of it. Many recent studies have focused on inorganic factors, such as metal nanoparticles, salts, and metal oxides. The advantages of inorganic factors include the ease with which they can be combined with ceramic and polymeric biomaterials. The following review focuses on hydroxyapatites substituted with ions with antibacterial properties. It considers materials that have already been applied in regenerative medicine (e.g., hydroxyapatites with silver ions) and those that are only at the preliminary stage of research and which could potentially be used in implantology or dentistry. We present methods for the synthesis of modified apatites and the antibacterial mechanisms of various ions as well as their antibacterial efficiency.